Infliximab efficacy and safety against refractory systemic necrotising vasculitides: long-term follow-up of 15 patients. Issue 9 (29th April 2008) - Josselin, L; Mahr, A; Cohen, P; Pagnoux, C; Guaydier-Souquières, G; Hayem, G; Job-Deslandre, C; Liferman, F; Pourrat, J; Guillevin, L
Abstract : Background: Results of uncontrolled studies have suggested that infliximab is efficacious against systemic necrotising vasculitides (SNV) refractory to conventional treatment. However, its safety and ability to induce and maintain remission over the long term remain unknown. Objectives: To report the use of infliximab to treat refractory SNV, focusing on patients' longer-term outcomes. Methods: The medical charts of patients given adjunctive infliximab for refractory SNV ⩾2 years before this evaluation were reviewed retrospectively. Results: The 15 patients (median age 46 (range 20–69) years, median follow-up 35 (24–41) months) included 10 with Wegener's granulomatosis, 1 microscopic polyangiitis, 3 rheumatoid arthritis-associated and 1 cryoglobulinaemia-related vasculitides. Infliximab was taken for a median time of 8 (2–31) months; 2 patients are still being treated. By day 45, 11 patients had entered remission (Birmingham Vasculitis Activity Score (BVAS) = 0) and 4 others had responded (BVAS decrease ⩾50%). Five patients achieved sustained remissions (⩾6 months, corticosteroids ⩽7.5 mg/day). Thirteen stopped infliximab because of loss of efficacy (n = 4), remission (n = 6) or non-compliance, chest tightness or side effect (1 each). Ten patients relapsed (median interval 13 months), 3 while still receiving infliximab; 2 were successfully re-treated with infliximab. Conclusion: These observations highlight infliximab as a potentially useful and safe salvage treatment for patients with refractory SNV.